Cosmopolitanism, Sovereignty and Global Justice in Light of Refugee Protection - BEREBON , Charles; ELUKE, Patrick (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This paper critically examines the concept of a “duty to aid and assist” as a necessary extension of ethical responsibility in global relations. It situates this duty within the framework of global economic interdependence and historical exploitation, arguing for a departure from traditional Rawlsian perspectives that focus narrowly on the establishment of just national institutions. Unlike the Rawlsian “duty to assist,” which prioritizes enabling burdened societies to become well-ordered, the “duty to aid and assist” integrates principles of global distributive justice, emphasizing the need to address systemic inequities arising from unequal starting positions, such as resource endowments and disproportionate bargaining powers in international trade. The paper highlights the limitations of Rawls’ assertion that political and social culture alone determine societal success, noting the critical role of historical and material advantages. It critiques the narrow scope of global egalitarianism, advocating instead for a duty that incorporates practical cut-off points for assistance, such as the eradication of global poverty and equitable burden-sharing for refugees and immigrants. These benchmarks are grounded in objective metrics like Gross National Income (GNI), military spending, and population density, providing a pragmatic yet ethical roadmap for global cooperation. Rather than advocating for indefinite financial transfers or perpetual assistance, this duty calls for a globally equitable distribution of responsibility, rooted in past injustices and present interdependence. It stresses that this obligation must be driven by a moral sense of duty, not philanthropy or charity, to ensure sustainability and avoid compassion fatigue. By framing aid and assistance as a collective, equitable responsibility, this paper contributes to the broader discourse on global justice and offers actionable strategies to foster a fairer international order.